2007
DOI: 10.3324/haematol.11118
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for detection of major phenotypic abnormalities in myelodysplastic syndromes: expression of CD56 in CMML

Abstract: Together with increase of proliferation potential, the myelodysplastic syndromes are characterised by qualitative abnormalities of differentiation of myeloid precursors associated with increased intramedullary apoptosis, resulting in peripheral cytopenia.1 FAB and WHO classifications of these syndromes, widely used among hematologists, are relatively robust and simple, but omit immunophenotyping for diagnosis. Immunophenotypic abnormalities are frequent in myelodysplastic syndromes.2 Yet interpretation of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…27 It has, however, been reported that, except for CD56, these abnormalities tend to be lost between the BM and PB because the disease resides in the BM, and for the fact that cells from the MDS clone are counter-selected to reach the PB compartment. 28 The same sensitivities and specificities as those already published 13,14 were obtained in this series of patients. Of note, Ogata score tended to be increased in RAEB1 and 2, demonstrating that, as reported by others, BM dysplasia detected in MFC increases with progression of the disease.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…27 It has, however, been reported that, except for CD56, these abnormalities tend to be lost between the BM and PB because the disease resides in the BM, and for the fact that cells from the MDS clone are counter-selected to reach the PB compartment. 28 The same sensitivities and specificities as those already published 13,14 were obtained in this series of patients. Of note, Ogata score tended to be increased in RAEB1 and 2, demonstrating that, as reported by others, BM dysplasia detected in MFC increases with progression of the disease.…”
Section: Discussionsupporting
confidence: 71%
“…Increased expression of CD56 has been previously reported in MDS and CMML. 28 Taking into account the expression of CD56 on monocytes improved the Ogata score, giving an efficient diagnosis of MDS/MPN. The expression of CD7 on myeloid progenitors was shown to be also informative in MDS, and this was later proven by other methods.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The most common aberrant immunophenotypic characteristics are overexpression of CD56, aberrant expression of CD2, decreased expression of CD14 and decreased expression of HLA-DR, CD13, CD15, CD64 and/or CD36. 26,27 Granulocytes may also show aberrant scatter properties and aberrant phenotypic features. An increased percentage of CD34 þ cells 22 or an emerging blast population with aberrant immunophenotype has been associated with early transformation to acute leukemia.…”
Section: May Respond To Lenalidomidementioning
confidence: 99%
“…Flow cytometry with CD14, CD11c, CD64 and immunohistochemistry with CD68 (KP-1), CD163 and CD68R (PG-M1) are less useful in confirming the presence of monocytic differentiation than cytochemistry (Figure 3e). 22,26,27 Additionally, by flow cytometric analysis, the blood and marrow monocytes usually express aberrant phenotypes with two or more aberrant features. 26,27 The most common aberrant immunophenotypic characteristics are overexpression of CD56, aberrant expression of CD2, decreased expression of CD14 and decreased expression of HLA-DR, CD13, CD15, CD64 and/or CD36.…”
Section: May Respond To Lenalidomidementioning
confidence: 99%
See 1 more Smart Citation